2016
DOI: 10.1038/srep34280
|View full text |Cite
|
Sign up to set email alerts
|

The scaffold protein Tks4 is required for the differentiation of mesenchymal stromal cells (MSCs) into adipogenic and osteogenic lineages

Abstract: The commitment steps of mesenchymal stromal cells (MSCs) to adipogenic and other lineages have been widely studied but not fully understood. Therefore, it is critical to understand which molecules contribute to the conversion of stem cells into differentiated cells. The scaffold protein Tks4 plays a role in podosome formation, EGFR signaling and ROS production. Dysfunction of Tks4 causes a hereditary disease called Frank-ter Haar syndrome with a variety of defects concerning certain mesenchymal tissues (bone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…Mice that lack functional SH3PXD2B due to a truncating mutation ( Nee [nose, eyes, ear], Figure b[v]) or gene KO (Figure b[vi]) are indistinguishable from their littermates at birth. After weaning, mutants develop growth retardation, craniofacial malformations that include brachycephaly, a short snout, exophthalmos, and excessive thoracic kyphosis (Dülk et al, ; Iqbal et al, ; Mao et al, ). Although about 20% of Sh3pxd2b KO mice died of unknown causes within their first weeks, the life span of surviving KO mice, as well as that of Nee mutants, is unaffected (Iqbal et al, ).…”
Section: Discussion and Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice that lack functional SH3PXD2B due to a truncating mutation ( Nee [nose, eyes, ear], Figure b[v]) or gene KO (Figure b[vi]) are indistinguishable from their littermates at birth. After weaning, mutants develop growth retardation, craniofacial malformations that include brachycephaly, a short snout, exophthalmos, and excessive thoracic kyphosis (Dülk et al, ; Iqbal et al, ; Mao et al, ). Although about 20% of Sh3pxd2b KO mice died of unknown causes within their first weeks, the life span of surviving KO mice, as well as that of Nee mutants, is unaffected (Iqbal et al, ).…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…Although about 20% of Sh3pxd2b KO mice died of unknown causes within their first weeks, the life span of surviving KO mice, as well as that of Nee mutants, is unaffected (Iqbal et al, ). In both mouse models, BMD was reduced and osteogenic differentiation was impaired (Dülk et al, ). The mice also had various cardiac abnormalities, including septal thinning and mitral valve defects (Iqbal et al, ).…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…Despite the similarities between Tks4 and Tks5, and the fact that Tks4 is also an important component of invadosome formation and function , care must be taken in ascribing all these developmental phenotypes to loss of podosomes. For example, recent research using a Tks4 knockout mouse revealed a differentiation defect in mesenchymal stromal cells (MSCs), caused by the reduced expression of RunX2 and Osterix, two osteogenic transcription factors that are normally up‐regulated during differentiation . In an adipogenic assay, Tks4 knockout MSCs were unable to form lipid droplets in the cytoplasm .…”
Section: Podosomes and Invadopodia Are Present In Diverse Cell Typesmentioning
confidence: 99%
“…Knockout of exon 4 of pNO40/PS1D in MSCs results in elevated ROS levels and p16 and Rb expression, consequently accelerating ageing and osteogenic differentiation defects . Similarly, MSCs isolated from Tks4 knock‐out mouse have reduced osteogenic and adipogenic differentiation capacities compared with those isolated from wild‐type mice . Although knockdown of NOX4 suppressed ROS production and adipogenic differentiation in MSCs, Kim et al demonstrated that NOX4 silencing did not inhibit MSC adipocyte differentiation.…”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
“…124 Similarly, MSCs isolated from Tks4 knock-out mouse have reduced osteogenic and adipogenic differentiation capacities compared with those isolated from wild-type mice. 125 Although knockdown of NOX4 suppressed ROS production and adipogenic differentiation in MSCs, 126 Kim et al 43 will we effectively regulate ROS levels to take advantage of the mass multiplication and strong differentiation capacities of MSCs, which will allow for harnessing the immortality of MSCs for transplantation and therapy in regenerative medicine.…”
Section: Pharmaceuticals For Ros Regulation In Mscsmentioning
confidence: 99%